IMPLEMENTASI DATABASE SECURITY MENGGUNAKAN KONSEP ROLE-BASED ACCESS CONTROL (RBAC) DALAM RANCANGAN DATABASE SISTEM INFORMASI MANAJEMEN SEKOLAH DENGAN POSTGRESQL - Arif, Achmad Yusron; Utami, Ema; Raharjo, Suwanto (Universitas Janabadra, 2019)
School management information system is an important application used to manage data and information of a school in order to provide the best service to the community. To create an effective and efficient information system, an effective database design is needed. This needs to be done because if the database is not designed properly, in the future when a system starts to develop, the integrity data stored in the database will decrease. One aspect that needs to be considered is database security. Database security is very important, because the data stored in the database is important information for schools, such as student, financial and employee data. One of the method that can be used to improve database security is Role-Based Access Control (RBAC), which is limiting access to users or roles according to their respective roles. In this study the RBAC method was applied in school management information systems using the PostgreSQL database. Keywords: Role Based Access Control, RBAC, Database Security, PostgreSQL, SIM Sekolah